Sarcopenia prevention in older adults: Effectiveness and limitations of non-pharmacological interventions - Doyoon Kim; Satoru Morikawa; Masashi Miyawaki; Taneaki Nakagawa; Sumito Ogawa; Yoshitaka Kase (Osteoporosis and Sarcopenia, 2025)
Sarcopenia is characterized by a decline in skeletal muscle mass, strength, and physical performance in older adults and is associated with reduced quality of life, an increased risk of requiring long-term care, and a significant economic burden on both patients and their families. In the context of global population aging, sarcopenia presents substantial health and social challenges. However, no effective pharmacological treatment has been established to date, and current management relies on non-pharmacological interventions. This review provides an overview of the most recent evidence on exercise, nutrition, and electrical muscle stimulation (EMS) as strategies to prevent the onset and progression of sarcopenia and discusses their effectiveness and limitations. Although the effectiveness of resistance training, alone or in combination with multicomponent exercise, has been demonstrated, the benefits of nutritional interventions and EMS remain limited. From a pathophysiological perspective, chronic inflammation has been identified as a key contributor to sarcopenia progression and is increasingly considered a potential therapeutic target. This review underscores the significance of a comprehensive intervention strategy tailored to the needs of the older population.